A mask-based infection control method for screening endoscopy may prevent SARS-CoV-2 transmission and relieve staff anxiety. (September 2021) - Nadatani, Yuji; Higashimori, Akira; Takashima, Shingo; Maruyama, Hirotsugu; Otani, Koji; Fukunaga, Shusei; Hosomi, Shuhei; Tanaka, Fumio; Fujii, Hideki; Nakano, Akemi; Taira, Koichi; Kamata, Noriko; et al.
Objectives: Endoscopy confers high risk for acquiring coronavirus disease 2019. Although guidelines recommend that medical staff use personal protective equipment, no infection control equipment have been established for patients. This study aimed to clarify the usefulness of two face masks we had designed for transnasal and transoral endoscopy. Methods: The efficacy of the masks was evaluated by simulating coughing in a mannequin with fluorescent dyes and mapping the droplet trajectory and number. The number of aerosols generated during endoscopy was clinically evaluated in the endoscopy room. Overall, 4356 screening endoscopies were performed with the patients wearing our masks at Medcity21, a health checkup facility, between June and December 2020; the effects of the masks on the patient's condition were evaluated retrospectively. An 11-item paper-based survey was performed by the endoscopy staff 6 months after the adoption of the mask-based infection control method. Results: Use of both masks reduced the number of droplets released during the simulation. Clinically, the use of both masks did not affect the patients' conditions during endoscopy and prevented an increase in the aerosols in the endoscopy room. This mask-based infection control method was favorably received, and all staff indicated that understanding the efficacy of our mask-based infection control reduced their anxiety regarding infection. Until December 2020, none of our staff had contracted SARS-CoV-2. Conclusion: Our mask-based infection control method is easy to adopt, inexpensive, and effective; understanding its effectiveness may help ease the fear of infection among endoscopy staff.